Molecular and Biological Characterization of Novel and Known Family Secoviridae Members Infecting Lettuce - Svanella-Dumas, Laurence; Tsarmpopoulos, Iason; Marais, Armelle; Faure, Chantal; Theil, Sébastien; Glasa, Miroslav; Predajna, Lukas; Gaudin, Jonathan; Tian, Sixing; Porcher, Laëtitia; Gentit, Pascal; De Oliveira, Milena Leite [UNESP]; et al. (Scientific Societies, 2023)
High-throughput sequencing of two lettuces showing virus-like symptoms in France provided evidence of infection by members of the family Secoviridae. One plant (JG1) had a complex mixed infection that involved, among others, a novel waikavirus (lettuce waikavirus 1) and two isolates of a sequivirus related to lettuce mottle virus (LeMoV). The second lettuce plant (JG2) was singly infected by LeMoV. Complete genomic sequences were obtained for all four isolates and, in addition, near complete genome sequences were obtained for other LeMoV or LeMoV-related isolates (from French cultivated and wild lettuces and from a Brazilian cultivated lettuce) and for two isolates of another family Asteraceaeinfecting sequivirus, dandelion yellow mosaic virus (DaYMV). Analysis of these genomic sequences allows the proposal of tentative genome organization for the various viruses and clarification of their phylogenetic relationships. Sequence and host range comparisons point to significant differences between the two sequivirus isolates identified in the JG1 plant and LeMoV isolates from France and Brazil, suggesting they belong to a novel species for which the name lettuce star mosaic virus is proposed.
Keywords: Brazil; etiology; France; high-throughput sequencing; lettuce; lettuce mottle virus